Hear Me Speak: Italian and Portuguese Women Facing Fisheries Management - Hall-Arber, Madeline (Anthropologica, 2022)
Declines in the principal groundfish stocks of New England led to the development of Amendment 5 to the New England Fishery Management Council’s Multispecies Management Plan. Implemented about a year and a half ago, Amendment 5 incorporated a phased-in series of increasingly strict management measures. Recently, however, the management council took a proposed Amendment 7 to public hearing, a series of extremely strict measures intending not only to halt over fishing, but to begin stock rebuilding. Two of the major groundfish ports in the northeast are Gloucester, dominated by first- and second-generation Italians, and New Bedford whose groundfish fleet is predominantly Portuguese. The women of the two ports face the same potential impacts associated with the current crisis in the fisheries. Loss of incomes, vessels and homes has already begun. When the public hearings for Amendment 7 were held, many Gloucester women attended and a number testified. In contrast, there were no Portuguese women at the hearing in New Bedford. In Gloucester, the women have transformed an organization that began as a campaign to promote cooking of underutilized species of fish into an active lobbying force, collaborative problem-solving agency and proactive civic group. No similar organization has arisen in New Bedford. This article postulates that, contrary to public opinion, ethnicity does not explain the differences in the activities of the women of these two ports, offers some alternative reasons and suggests why these are significant for fisheries management